Inhibition of SARS-CoV-2 in Vero cell cultures by peptide-conjugated morpholino-oligomers - Rosenke, Kyle (bioRxiv, 2020)
BACKGROUND: SARS-CoV-2 is the causative agent of COVID-19 and a pathogen of immense global public health importance. Development of innovative direct-acting antiviral agents is sorely needed to address this virus. Peptide-conjugated morpholino oligomers (PPMO) are antisense agents composed of a phosphordiamidate morpholino oligomer covalently conjugated to a cell-penetrating peptide. PPMO require no delivery assistance to enter cells and are able to reduce expression of targeted RNA through sequence-specific steric blocking. OBJECTIVES AND METHODS: Five PPMO designed against sequences of genomic RNA in the SARS-CoV-2 5’-untranslated region and a negative control PPMO of random sequence were synthesized. Each PPMO was evaluated for its effect on the viability of uninfected cells and its inhibitory effect on the replication of SARS-CoV-2 in Vero-E6 cell cultures. Cell viability was evaluated with an ATP-based method and viral growth was measured with quantitative RT-PCR and TCID (50) infectivity assays. RESULTS: PPMO designed to base-pair with sequence in the 5’-terminal region or the leader transcription regulatory sequence-region of SARS-CoV-2 genomic RNA were highly efficacious, reducing viral titers by up to 4-6 log10 in cell cultures at 48-72 hours post-infection, in a non-toxic and dose-responsive manner. CONCLUSION: The data indicate that PPMO have the ability to potently and specifically suppress SARS-CoV-2 growth and are promising candidates for further pre-clinical development.